In-vivo antiparasitic assessment and toxicity evaluation of Curcuma longa against the growth and survival of Trypanosoma evansi - Baba, Mohd Shukri; Roslan, Mohamad Farid (2018)
Realizing that Trypanosoma evansi is now has been potentially trans-infected to human from animals, this study demonstrated how the manipulation of natural spice, Curcuma longa (turmeric), promisingly can solve the endemicity of vector-borne zoonotic manifestation of atypical human trypanosomiasis (AHT) and Surra disease in livestock. The effectiveness of C. longa roots on the growth and survival of the haemoflagellate protozoa Trypanosoma evansi was compared with Berenil (C18H22N8O3). Groups of male ICR mice (6 – 8 weeks old, 20 – 25g body weight) were intraperitoneally (i.p) administered with the parasite at 5.0 × 103 T. evansi/mouse and orally given pre- and post-infection treatments with10 µg/mL of C. longa-dH2O extract at 0.1 mL/mouse. Using Giemsa stained blood smear and examined under light and scanning electron microscopes (SEM), the morphological changes of parasite cells were assessed. Toxicity level of blood enzymes and selected vital organs and survival rate of the mice were also investigated. The morphological changes of T. evansi cells were evidenced. The cell became crescent-shaped and the undulating membrane was destroyed where both posterior and anterior ends were tapered before the flagellum disintegrated in which lead to death of the cells. A positive correlation (p ≤ 0.05, n = 6) were recorded between the mice survival time and the ability to inhibit the parasites growth in pre-infection treatment group. Besides, the mice in PRE14 group (daily treated with C. longa-dH2O extract from 14 days before infection) was also recorded the longest pre-patent (39.15 ± 3.3 days) and survival (228.75 ± 2.6 days) period. Except for AST level for sub-acute regime group which was a bit elevated, the results for biochemical tests were significantly situated in the normal ranged level for all regimens as well as no abnormalities and injuries found on the selected vital organs. This study significantly evidenced that C. longa could be manipulated as a potential antitrypanosomal alternative drug for the preservation and welfare of human and livestock beings.